A comparative study of granisetrone, dexamethasone and combination of granisetrone-dexamethasone as prophylaxis for postoperative nausea vomiting during laparoscopic surgeries - Chilana, Deep; Rastogi, Bhawana; Kumar, Abhishake; Singh, Brig V.P.; Arora, Richa; Gupta, Anshul (International Journal of Research in Medical Sciences, 2019)
Background: In laparoscopic surgeries, insufflation with carbon dioxide triggers vagal afferents on the bowel and peritoneum which induces emesis by activating the vomiting center. It is hypothesized that combined antiemetics with different sites of activity would be more effective than one drug alone for the prophylaxis against PONV. So, the present study was planned to compare the efficacy of granisetron, dexamethasone and combination of granisetron with dexamethasone to prevent PONV. Methods: This randomized prospective double-blind study was performed on 120 patients, aged between 18 and 58 years of ASA physical status I and II of either sex undergoing laparoscopic surgeries under general anesthesia. Patients were randomized in three groups, group I (granisetrone 2 mg I.V.), group II (dexamethasone) 8 mg I.V., group III (granisetrone+dexamethasone) 2 mg+8 mg I.V. with 40 patients in each group. Complete response, incidence of nausea, vomiting, and rescue antiemetic were recorded at specified intervals. Results: A complete response (defined as no PONV and no need for another rescue antiemetic) was achieved in 75% of the patients given granisetron, 70% in dexamethasone and in 92.5% of the patients given granisetron plus dexamethasone (P <0.05). The overall cumulative incidences (0-24 hours) of PONV were 10 (25%) in the granisetron, 12 (30%) in the dexamethasone and 3 (7.5%) in the combination group. No difference in adverse events were observed in any of the groups. Conclusions: The prophylactic therapy of granisetron 2 mg plus dexamethasone 8 mg just before induction of anaesthesia is significantly effective in prevention of PONV in patients undergoing laparoscopic surgeries.